Large-Scale Extraction and Purification of Microcystin-LR by Macroporous Resins - Cao, Y.Q.; Wei, N.; Gong, A.J.; Qiu, L.N. (Asian Journal of Chemistry, 2014)
An effective method for large-scale extraction and purification of microcystin-LR (MC-LR) was established. 660 mL supernatant centrifugated from algae serum was absorbed by resin D101. The impurities on D101 resin were removed by 40 % acetic acid (3 L), deionized water (2.5 L), 20 % acetone (2 L) and 10 % ethanol (2 L) in turn. Thus microcystin-LR on D101 resin was purified. The adsorbed microcystin-LR was eluted from the resin with 70 % methanol (9 L). The eluent was concentrated by rotary evaporation at 80 °C. The quality of microcystin-LR in the crude extract was 2075.5 μg. The recovery rate was 79.71 %. In addition, the method of getting microcystin-LR by preparative chromatography is established. The purity of the product was 95 %.